Kualiti Air dan Nutrien di Tanah Bencah BIOECODS, Kampus Kejuruteraan Universiti Sains Malaysia, Nibong Tebal, Pulau Pinang: Water Quality and Nutrient in BIOECODS Wetland, Engineering Campus, Universiti Sains Malaysia, Nibong Tebal, Pulau Pinang - Ayob, Nor Adilah; Zaini, Masitah; Musa, Noor Musfirah; Mohd Najib, Sumayyah Aimi; Ismail, Wan Ruslan (GEOGRAFI, 2017)
Bio-ecological Drainage systems (BIOECODS) is one of the constructed wetlands that play a role in regulating all the nutrients and treat storm water quality. A study of water quality parameters from every pool in the ecological component of BIOECODS was conducted from September 2014 to February 2015 which involved sampling for every two weeks to identify changes in quality of the BIOECODS system. Among the parameters of water quality measured on BIOECODS wetlands is the total suspended solids (TSS), namely nitrite-nitrogen (NO2-N), nitrate-nitrogen (NO3-N), and ammonia-nitrogen (NH3-N). Parameter physicochemical characteristics studied were turbidity, conductivity, total dissolved solids, temperature, dissolved oxygen, and pH. The results showed that the content of TSS in Wetpond station (WP) is the highest while the Recreational Pond (RP) station is the lowest. The WP, TSS content was 14.22 ± 5.58 mg/L and in RP of 3.93 ± 1.60 mg/L. Meanwhile, the nitrite concentration in WP station was 0.37 ± 0.013 mg/L and RP station was 0.09 ± 0.0065 mg/L. Nitrate concentrations in WP station was 0.24 ± 0.19 mg/L and nitrate concentration in the RP was 0.060 ± 0.03 mg/L. The concentration of ammonia in the WP station was 0.19 ± 0.06 mg/L and the Rp station was 0.14 ± 0.04 mg/L. The finding showed that the BIOECODS wetland system play an important role in regulating nutrients and maintain good water quality. In addition, BIOECODS is also effective in filtering storm water runoff and waste water received from all over the campus.